Fourth Graders’ Perceptions of the Use of Reciprocal Teaching Model in English Reading Comprehension - Tham, Duong My; Sang, Nguyen Thi Thu (VNU Journal of Science: Education Research; Vol 37 No 4, 2021)
Developing reading skills plays one of the vital roles in teaching EFL learners, especially young learners; however, not all teaching models and approaches can be properly employed in teaching young learners. The mixed-methods study endeavours to explore fourth graders’ perceptions of the use of the reciprocal teaching model (RTM) in learning English reading comprehension at a Ho Chi Minh City-based international school. A cohort of fifty students were involved in answering the questionnaire, and fiusefteen of them participated in semi-structured interviews. The quantitative data from the questionnaire were processed by SPSS in terms of descriptive statistics, and the qualitative data from interviews were analysed using the content analysis approach. The findings showed that participants believed that the use of RTM impacted positively their English reading comprehension. They could foster the use of reading strategies and improve their vocabulary and reading comprehension ability. Such preliminary findings can help to further research to confirm the effectiveness of RTM in teaching reading comprehension to EFL learners in general and young learners in specific.